DEVELOPING ELT MATERIALS FOR MANAGEMENT STUDENTS AT STIE YPUP MAKASSAR - Nurpahmi, Sitti; Prasetyo, Muhammad Zukri; Yaumi, Muhammad (elstic : english language linguistics culture, 2023)
This research aimed at developing Insurance and Budgeting Organization English Material for students of Management Department at STIE YPUP, Makassar. The research design used in this study was Research and Development (R&D). The development model used was ISD model. It consisted of three phases: needs analysis, instructional design, implementation, and evaluation. T Types of data obtained in this study were quantitative and qualitative data. The instruments used in this research were questionnaire and observation sheet for two experts. In this research, two experts were involved in order to validate the product. There were three systematic aspects that they validated of the product: Materials Systematic Organization, Systematic English Teaching and Systematic Content of English. The development of English materials includes conceptual map, goals, materials sequence, English material and worksheet, and additional task. The product was tried out to the first semester of students of management department at STIE YPUP. Therefore, the result indicated that based on the experts’ judgment as well as try-out design result, the developed ELT materials were applicable to be taught at the first semester of students of management department as topics in English for them.